Milk protein-based active edible packaging for food applications: An eco-friendly approach - Chaudhary, Vandana; Kajla, Priyanka; Kumari, Parveen; Bangar, Sneh Punia; Rusu, Alexandru; Trif, Monica; Lorenzo, Jose M. (Frontiers in Nutrition, 2022)
Whey and casein proteins, in particular, have shown considerable promise in replacing fossil-based plastics in a variety of food applications, such as for O2 susceptible foods, thereby, rendering milk proteins certainly one of the most quality-assured biopolymers in the packaging discipline. Excellent gas barrier properties, proficiency to develop self-supporting films, adequate availability, and superb biodegradability all these properties aroused great attention towards whey and other milk proteins in recent years. High thermal stability, nontoxicity, the ability to form strong inter cross-links, and micelle formation, all these attributes make it a suitable material for outstanding biodegradability. The unique structural and functional properties of milk proteins make them a suitable candidate for tailoring novel active package techniques for satisfying the needs of the food and nutraceutical industries. Milk proteins, especially whey proteins serve as excellent carriers of various ingredients which are incorporated in films/coatings to strengthen barrier properties and enhance functional properties viz. antioxidant, antimicrobial. In this review, the latest techniques pertaining to the conceptualization of active package models/ systems using milk proteins have been discussed. Physical and other functional properties of milk protein-based active packaging systems are also reviewed. This review provides an overview of recent applications of milk protein-sourced active edible packages in the food packaging business.